Induction of resilience strategies against biochemical deteriorations prompted by severe cadmium stress in sunflower plant when Trichoderma and bacterial inoculation were used as biofertilizers - Abeed, Amany H. A.; Mahdy, Rasha E.; Alshehri, Dikhnah; Hammami, Inès; Eissa, Mamdouh A.; Abdel Latef, Arafat Abdel Hamed; Mahmoud, Ghada Abd-Elmonsef (Frontiers in Plant Science, 2022)
Background Cadmium (Cd) is a highly toxic heavy metal. Its emission is suspected to be further increased due to the dramatic application of ash to agricultural soils and newly reclaimed ones. Thereby, Cd stress encountered by plants will exacerbate. Acute and chronic exposure to Cd can upset plant growth and development and ultimately causes plant death. Microorganisms as agriculturally important biofertilizers have constantly been arising as eco-friendly practices owing to their ability to built-in durability and adaptability mechanisms of plants. However, applying microbes as a biofertilizer agent necessitates the elucidation of the different mechanisms of microbe protection and stabilization of plants against toxic elements in the soil. A greenhouse experiment was performed using Trichoderma harzianum and plant growth-promoting (PGP) bacteria (Azotobacter chroococcum and Bacillus subtilis) individually and integrally to differentiate their potentiality in underpinning various resilience mechanisms versus various Cd levels (0, 50, 100, and 150 mg/kg of soil). Microorganisms were analyzed for Cd tolerance and biosorption capacity, indoleacetic acid production, and phosphate and potassium solubilization in vitro. Plant growth parameters, water relations, physiological and biochemical analysis, stress markers and membrane damage traits, and nutritional composition were estimated. Results Unequivocal inversion from a state of downregulation to upregulation was distinct under microbial inoculations. Inoculating soil with T. harzianum and PGPB markedly enhanced the plant parameters under Cd stress (150 mg/kg) compared with control plants by 4.9% and 13.9%, 5.6% and 11.1%, 55.6% and 5.7%, and 9.1% and 4.6% for plant fresh weight, dry weight, net assimilation rate, and transpiration rate, respectively; by 2.3% and 34.9%, 26.3% and 69.0%, 26.3% and 232.4%, 135.3% and 446.2%, 500% and 95.6%, and 60% and 300% for some metabolites such as starch, amino acids, phenolics, flavonoids, anthocyanin, and proline, respectively; by 134.0% and 604.6% for antioxidants including reduced glutathione; and by 64.8% and 91.2%, 21.9% and 72.7%, and 76.7% and 166.7% for enzymes activity including ascorbate peroxidase, glutathione peroxidase, and phenylalanine ammonia-lyase, respectively. Whereas a hampering effect mediated by PGP bacterial inoculation was registered on levels of superoxide anion, hydroxyl radical, electrolyte leakage, and polyphenol oxidase activity, with a decrease of 0.53%, 14.12%, 2.70%, and 5.70%, respectively, under a highest Cd level (150 mg/kg) compared with control plants. The available soil and plant Cd concentrations were decreased by 11.5% and 47.5%, and 3.8% and 45.0% with T. harzianum and PGP bacterial inoculation, respectively, compared with non-inoculated Cd-stressed plants. Whereas, non-significant alternation in antioxidant capacity of sunflower mediated by T. harzianum action even with elevated soil Cd concentrations indicates stable oxidative status. The uptake of nutrients, viz., K, Ca, Mg, Fe, nitrate, and phosphorus, was interestingly increased (34.0, 4.4, 3.3, 9.2, 30.0, and 1.0 mg/g dry weight, respectively) owing to the synergic inoculation in the presence of 150 mg of Cd/kg. Conclusions However, strategies of microbe-induced resilience are largely exclusive and divergent. Biofertilizing potential of T. harzianum showed that, owing to its Cd biosorption capability, a resilience strategy was induced via reducing Cd bioavailability to be in the range that turned its effect from toxicity to essentiality posing well-known low-dose stimulation phenomena (hormetic effect), whereas using Azotobacter chroococcum and Bacillus subtilis, owing to their PGP traits, manifested a resilience strategy by neutralizing the potential side effects of Cd toxicity. The synergistic use of fungi and bacteria proved the highest efficiency in imparting sunflower adaptability under Cd stress.